Optimalisasi Lembaga Adat Desa Meneguhkan Konstitusionalisme - Hamamah, Fatin; Sarip, Sarip (Pagaruyuang Law Journal, 2019)
The village as the basis of national development in upholding new constitutionalism found a bright spot as the birth of the Village Customary Institution (LAD) which had a noble task. Village customary life is determined, mobilized, and controlled by institutions in the village. Village life loses its identity as a village, individuals, communities and villages move in conditions of individualism. Customary law is a term that is given legal knowledge, as guidelines, reality that governs groups, and disciplines people's lives in Indonesia. Indonesian people living in remote areas need order and guidance as rules they make themselves. Thus the existence of customary law to date still has an important role, especially in the formation of future national laws, especially in the field of family law. Customary law will be one of the main sources in the formation of written law, so that written rules are automatically a reflection of community law. And of course with the expectation that when the written law is enacted, there is no gap in practice in the community.